Risk factors for bronchopulmonary dysplasia in five portuguese neonatal intensive care units - Guimarães, H (2012)
The pathogenesis of bronchopulmonary dysplasia (BPD) is clearly multifactorial. Specific pathogenic risk factors are prematurity, respiratory distress, oxygen supplementation, mechanical ventilation (MV), inflammation, patent ductus arteriosus (PDA), etc. AIM: To evaluate BPD prevalence and to identify risk factors for BPD in five Portuguese Neonatal Intensive Care Units in order to develop better practices the management of these newborns. MATERIAL AND METHODS: 256 very low birth weight infants with gestational age (GA) <30 weeks and/or birthweight (BW) <1250 g admitted in five Portuguese NICUs, between 2004 and 2006 were studied. A protocol was filled in based on clinical information registered in the hospital charts. BPD was defined as oxygen dependency at 36 weeks of postconceptional age. RESULTS: BPD prevalence was 12.9% (33/256). BPD risk decreased 46% per GA week and of 39% per 100g BW. BPD risk was significantly higher among newborns with low BW (adj OR= 0.73, 95% CI=0.57- 0.95), severe hyaline membrane disease (adj OR= 9.85, 95% CI=1.05-92.35), and those with sepsis (adj OR=6.22, 95% CI=1.68-23.02), those with longer duration on ventilatory support (42 vs 3 days, respectively in BPD and no BPD patients, p <0.001) and longer duration of FiO2>0.30 (85 vs 5 days, respectively in BPD and no BPD patients, p <0.001). COMMENTS: The most relevant risk factors were low birth weight, severe hyaline membrane disease, duration of respiratory support and oxygen therapy, and nosocomial sepsis. The implementation of potentially better practices to reduce lung injury in neonates must be addressed to improve practices to decrease these risk factors.